Decreased cerebral oxygen saturation levels during direct laryngoscopy with spontaneous ventilation in children. (October 2020) - Wasserzug, Oshri; Fishman, Gadi; Handzel, Ophir; Stockie, Daniel; Oestreicher-Kedem, Yael; Fliss, Dan M.; DeRowe, Ari
Abstract: Introduction: Direct laryngoscopy in children is usually performed with spontaneous ventilation and monitored by pulse oximetry. It is currently unknown if spontaneous ventilation has an effect on cerebral oxygenation. We hypothesized that cerebral oxygenation may be impeded during direct laryngoscopy with spontaneous ventilation in children. Objective: Our objective was to determine if children who undergo direct laryngoscopy under general anesthesia with spontaneous breathing experience significant reductions in cerebral oxygen saturation levels, and whether or not these reductions are accompanied by decreases in peripheral oxygen saturation levels. Methods: This pilot study included 16 consecutive children who underwent direct laryngoscopy under general anesthesia and spontaneous ventilation. The INVOS™ system, which is currently used to monitor cerebral oxygen saturation levels during neurosurgery and cardiothoracic surgery, consists of a processing unit and 2 sensors that are applied to the patient's forehead. We used it to record cerebral oxygenation levels throughout the procedure. Peripheral pulse oximetry was recorded simultaneously, and the results were compared to the levels recorded by the INVOS™ system. Results: Cerebral oxygen saturation levels decreased by more than 20% from baseline in 7/10 children with tracheostomy and in 2/6 children without tracheostomy, while peripheral oxygen saturation levels remained intact in all the children. The mean time from induction of anesthesia to significant decrease in the cerebral oxygenation level (rSO2) was 14 ± 6 min for the tracheostomy group and 14.5 ± 1.5 min for the no tracheostomy group. Conclusions: Children who undergo direct laryngoscopy under general anesthesia with spontaneous ventilation may display reductions in brain oxygenation levels that are not detected by standard pulse oximetry, which reflects only peripheral oxygenation levels. Further study is required to explore the possible effect of this phenomenon in children who undergo direct laryngoscopy.